Faktor Penyebab Keterlambatan Pengembalian Dokumen Rekam Medis di RS X Kabupaten Kediri - Sayyidah Mirfat; Nurwulan Andadari; Yetty Nusaria Nawa Indah (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2017)
The purpose of this study was to determine the root problem of any late return of inpatient medical records documents in X Hospital. This research was conducted with a qualitative descriptive approach with the method of observation, in-depth interviews and time motion study. Determining root of the problem is done by brainstorming with the hospitals staff with USG method (urgency, seriousness, growth). Root problem that contribute to delay return of inpatient medical records are indiscipline doctor in filling out medical records especially medical resumes; some doctor are not making patient visit every day, so the order was given by phone; and sometime nurses forgot to remind the doctor to fill out a medical resume and signature. Other factors affecting the delay are method, money, material dan machine factors.